Ilmu sebagai Kunci Kesuksesan Dunia dan Akhirat Menurut Al-Quran dan Hadist - Muhammad Zainul Arifin; Ainur Rofiq Sofa (Universitas Maritim AMNI Semarang, 2024)
Knowledge plays a central role in Islamic teachings, both as a means to achieve worldly success and salvation in the afterlife. This study aims to examine the virtue of knowledge as the key to worldly and afterlife success based on the perspective of the Qur'an and hadith. The method used is a literature review with a thematic interpretation approach and hadith analysis to examine the verses of the Qur'an and hadiths related to knowledge. The results of the study show that the Qur'an and hadith firmly place knowledge in a very high position, with knowledge being the main factor that elevates human status, both in the world and in the afterlife. In Surah Al-Mujadilah verse 11, Allah SWT states that He will elevate the status of those who have knowledge, while the hadiths of the Prophet Muhammad SAW emphasize that knowledge is the path to heaven and good deeds whose rewards continue to flow. Knowledge not only leads to worldly achievements such as social, economic, and technological progress, but also becomes the main foundation for carrying out worship properly and obtaining happiness in the afterlife.